2012
DOI: 10.1111/j.1465-3362.2012.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and its impact on the risk of high blood pressure in Russia

Abstract: Prevention policies as well as government programs aimed at treating alcohol-related health outcomes should take into consideration the significant adverse effect of alcohol consumption on high blood pressure. It is also recommended that policy interventions aimed to address alcohol addiction issues in Russia explicitly differentiate between vodka and beer drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(47 reference statements)
1
5
0
1
Order By: Relevance
“…The odds of developing hypertension among those who drank alcohol was three times prone to hypertension than their counterparts. This finding was supported by other research findings alcohol consumption is a risk factor for hypertension [20, 25, 26]. This might be due to alcohol consumption is associated with cardiovascular diseases including hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…The odds of developing hypertension among those who drank alcohol was three times prone to hypertension than their counterparts. This finding was supported by other research findings alcohol consumption is a risk factor for hypertension [20, 25, 26]. This might be due to alcohol consumption is associated with cardiovascular diseases including hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…About 81% of the rural study population reported regular alcohol consumption. Previous research indicated that heavy alcohol consumption was a risk factor for high blood pressure [ 30 32 ]].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, alcohol, which in this case equates to liquor (alcohol without antioxidants, resveratrol), has been associated with suppressed bioavailability of nitric oxide. In addition, antioxidants and other secondary components of wine and beer can also enhance flow-mediated vasodilatation [28] [29] . Yet, it is important to remember that for those individuals consuming more than 3 drinks of wine or beer daily the beneficial effects disappear, probably because the balance between alcohol and antioxidants is lost.…”
Section: Discussionmentioning
confidence: 99%